Experimental Evaluation of Thermohydraulic Performance of Tubular Solar Air Heater - Yousif Fateh Midhat; Issam Mohammed Ali Aljubury (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The thermohydraulic performance of a new design solar air heater (SAH) design was examined experimentally in this paper as a trial to improve the flat-plate SAH’s efficiency. A flat-plate solar air heater (FPSAH) and a jacketed tubular solar air heater (JTSAH) having similar dimensions were constructed to compare their thermal performance efficiencies. A band of Aluminum jacketed tubes were arranged side by side in parallel to the airflow direction to form the absorber of a jacketed tubular solar air heater (JTSAH). The experiments were accomplished at three mass flow rates (MFR)s: 0.011 kg/s. 0.033 kg/s, and 0.055 kg/s. Results revealed that the maximum temperature difference was obtained from JTSAH at 38°C in comparison to 32°C from the FPSAH at MFR of 0.011 kg/s. The thermal losses from the upper glass cover of the JTSAH were less than the same losses at the FPSAH due to the reduced absorber and glass temperatures of the JTSAH. The gained power was higher at the JTSAH than the FPSAH. At the JTSAH, at 0.055 kg/s MFR, the maximum average thermal efficiency obtained was 81%, and the maximum average thermos-hydraulic efficiency obtained was 75.61 %. It is noted that increasing the MFR increases the thermal efficiency, also, its optimum value rises the thermos-hydraulic efficiency to a specific optimum point. The pressure drop increases with the MFR and JTSAH compared to the FPSAH